KONFIGURASI POLITIK DAN KEBERPIHAKAN REGULASI DAERAH BIDANG HAK EKONOMI, SOSIAL DAN BUDAYA PADA MASYARAKAT MARJINAL DI KALIMANTAN BARAT - Rahmad Satria (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2015)
This research aimed to evaluate and describe the political configuration of regional government and alignment of regional regulations which regulate the fulfillment of ecosoc rights of marginalized societies in West Kalimantan. By means of socio-legal approach, this research founds the fact of political configuration of Regional Government of West Kalimantan that is classified as democratic, does not automatically produces some regional regulation which stand up for (responsive) the fulfillment of ecosoc rights of marginalized societies. The Identification of its causes is regulatory problem due to the lack of unity of regulations which are synchronized and consistent, the low perception of both regional government and societies toward the existence of the fulfillment of ecosoc rights and the factor of absence of political will to regulate the regional regulations that based on alignment for marginalized societies. Ideally, the construction of regional regulations is not committed in discriminative and always accommodate the normative basic of human rights.